2003
DOI: 10.1103/physrevb.68.201308
|View full text |Cite
|
Sign up to set email alerts
|

Layer-charge instability in unbalanced bilayer systems in the quantum Hall regime

Abstract: Measurements in GaAs hole bilayers with unequal layer densities reveal a pronounced magnetoresistance hysteresis at the magnetic field positions where either the majority or minority layer is at Landau level filling factor one. At a fixed field in the hysteretic regions, the resistance exhibits an unusual time dependence, consisting of random, bidirectional jumps followed by slow relaxations. These anomalies are apparently caused by instabilities in the charge distribution of the two layers.PACS numbers: 71.7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
33
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 10 publications
13
33
0
Order By: Relevance
“…These hysteretic effects have been associated with a number of physical phenomena, including non-equilibrium charge distributions [3][4][5] , long-lived eddy currents [6][7][8][9] within the interior of the 2DES, first order phase transitions involving the electron spin [10][11][12][13][14][15] or pseudospin [16][17][18][19] degrees of freedom, and metastable orientations of the electron nematic phases at high Landau level occupancy 20 . In the majority of these experiments the behavior of the collective electron state was inferred from measurements of magnetoresistance, which was found to depend strongly on the sweep rate and direction of the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…These hysteretic effects have been associated with a number of physical phenomena, including non-equilibrium charge distributions [3][4][5] , long-lived eddy currents [6][7][8][9] within the interior of the 2DES, first order phase transitions involving the electron spin [10][11][12][13][14][15] or pseudospin [16][17][18][19] degrees of freedom, and metastable orientations of the electron nematic phases at high Landau level occupancy 20 . In the majority of these experiments the behavior of the collective electron state was inferred from measurements of magnetoresistance, which was found to depend strongly on the sweep rate and direction of the magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…This hysteretic electronic transport was first observed in a single, high electron mobility quantum well with a low mobility parallel conducting channel 12 , and later in hole DQW structures 13 . So far, no studies have been conducted in the most common DQW structures, the electron DQW's.…”
mentioning
confidence: 99%
“…Recently, a new phenomenon has been discovered in the DQW structures: electronic transport hysteresis 12,13 . It was observed that, when the densities of two wells are different and tunneling is negligible, the magnetotransport coefficients show hysteretic behavior when the magnetic (B) field is swept up and down.…”
mentioning
confidence: 99%
“…In addition, since the distance (or the coupling) between the two quantum wells can be controllably tuned from a few tenths of nanometer to several microns, DQW structures have shown promise as possible future electronic devices for next generation information processing 11 . Recently, a new phenomenon has been discovered in the DQW structures: electronic transport hysteresis 12,13 . It was observed that, when the densities of two wells are different and tunneling is negligible, the magnetotransport coefficients show hysteretic behavior when the magnetic (B) field is swept up and down.…”
mentioning
confidence: 99%